2015
DOI: 10.4137/cmo.s22456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tamoxifen and Raloxifene on the Proliferative Activity of the Breast Epithelium in Premenopausal Women

Abstract: OBJECTIVESTo compare the effects of tamoxifen and raloxifene on the proliferative activity of normal breast tissue in premenopausal women as measured by Ki-67/MIB-1 expression.STUDY DESIGNA total of 48 women with benign breast nodules and a recommendation for surgical removal of the lesion took part in this study. They were randomized to use tamoxifen or raloxifene for 22 days, after which they were submitted to surgery. During the surgical procedure, a 1-cm fragment of normal breast tissue was removed to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Two of the studies analyzed reported a significant change in the mean Ki-67 expression following treatment with acolbifene ( 53 ) and with raloxifene ( 62 ). Interestingly, while Ki-67 was not measured at the pre-treatment stage in the study carried out by Lucato et al ( 63 ), its post-treatment expression was low and there were no significant differences between the raloxifene and tamoxifen therapies tested. In general, the results of the studies analyzed so far reveal that acolbifene, raloxifene and tamoxifen each produce an important anti-proliferative effect.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Two of the studies analyzed reported a significant change in the mean Ki-67 expression following treatment with acolbifene ( 53 ) and with raloxifene ( 62 ). Interestingly, while Ki-67 was not measured at the pre-treatment stage in the study carried out by Lucato et al ( 63 ), its post-treatment expression was low and there were no significant differences between the raloxifene and tamoxifen therapies tested. In general, the results of the studies analyzed so far reveal that acolbifene, raloxifene and tamoxifen each produce an important anti-proliferative effect.…”
Section: Discussionmentioning
confidence: 85%
“…The Ki-67 antigen was analyzed before treatment and at the treatment’s end point in just 3 of the 7 studies, obtaining results that reached statistical significance (P<0.001) in only 2 studies. In the study by Lucato et al ( 63 ), the Ki-67 antigen was not measured before treatment, yet the values obtained after treatment were not significantly different between the two groups. Likewise, the results presented in the study by Serrano et al were also not significant (P=0.78), whereas the studies by Eng-Wong et al , Decensi et al and Bramwell et al ( 64 - 66 ) did not evaluate the Ki-67 antigen.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Ki‐67 antibodies are used as a predicting factor for treatment response when evaluating different therapies for breast cancer. The capacity to reduce tumor cell proliferation, as measured by Ki‐67 expression, is considered to be a good marker of the efficacy of the agents studied .…”
Section: Discussionmentioning
confidence: 99%
“…However, uptake and adherence to daily oral TMX are relatively low [ 5 ]. Raloxifene (RLX), another SERM like TMX, was originally developed to treat osteoporosis in postmenopausal women [ 5 ], but in 2007, the US Food and Drug Administration (FDA) approved the use of RLX to reduce invasive BC risk in postmenopausal women with osteoporosis and/or at high risk for BC [ 9 , 10 ]. Compared to TMX, RLX has a preferable safety profile with no increased risk for endometrial cancer and less risk for thromboembolism [ 5 ], making it an ideal first-line drug to use in a sustained delivery platform for chemoprophylaxis.…”
Section: Introductionmentioning
confidence: 99%